Pemanfaatan Pupuk Cair dan Biochar Terhadap Pertumbuhan Tanaman Sawi (Brassica Juncea L.) - Setia Murni Telaumbanua; Karunia Gea; Leonardus Historis Manao; Mohamad Yunus Laia; Bimerdin Daely; Mariwantuti Waruwu (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to determine the effect of liquid biofertilizer and biochar on the growth and yield of mustard greens (Brassica juncea). This study was conducted from November to December 2023 in the Agrotechnology practicum field, Faculty of Science and Technology, Nias Raya University. The experimental design used was a 3 x 4 factorial Randomized Block Design (RAK) with 3 replications. There were two factors studied, namely the concentration of liquid biofertilizer consisting of three levels, namely Control (P0), 75 ml (P1), and 150 ml (P2), and biochar consisting of 4 levels, namely Control (B1), 1kg (B2), 2kg (B2) and 3kg (B3). The variables observed included plant height, number of leaves, and leaf length, leaf width, and wet weight. The concentration of liquid biofertilizer had a significant effect on leaf length, leaf width, and wet weight of plants aged 35 HST, had no significant effect on plant height, number of leaves aged 7, 14, 21, and 28 HST. The best dose of liquid biofertilizer treatment was at a concentration of 150 ml (P2). The provision of biochar had a significant effect on leaf length, leaf width, and plant wet weight at the age of 35 HST, had no significant effect on plant height and number of leaves at the ages of 7, 14, 21, and 28 HST. The results showed that there was a significant interaction on leaf length, leaf width, and plant wet weight, a significant interaction on leaf length, leaf width, and plant wet weight at the age of 35 HST, while other parameters had no significant effect. The interaction between the concentration of liquid fertilizer 150 ml (P2) with 3 kg of biochar (B3) was the best treatment combination.